Fibroblast growth factor receptor risk signature predicts patient prognosis and immunotherapy resistance in colorectal cancer - Li, Xiaofang; Pan, Zhiling; Luan, Tiankuo; Xiao, Qian; Li, Liuying; Wu, Qianxue; Yao, Guoqing; Zhang, Xiang; Song, Daqiang (Frontiers in Immunology, 2024)
BackgroundFibroblast Growth Factor Receptor (FGFR) signaling is linked with tumor progression and tumor immunoevasion, yet the potential effect of FGFR signature on the prognosis of patient with colorectal cancer (CRC) and response to immune therapy remains elusive.MethodsThe fibroblast growth factor receptor risk signature (FRS) was identified through single-cell RNA sequencing, bulk RNA sequencing, and machine learning techniques. Signaling enrichment analyses were conducted using Gene Set Enrichment Analysis (GSEA) and the Kyoto Encyclopedia of Genes and Genomes (KEGG). Drugs targeting the FRS were predicted using the Cancer Therapeutics Response Portal (CTRP) and PRISM databases. The analysis of T cell function and the tumor microenvironment (TME) was performed using flow cytometry.ResultsIn this study, we characterized the FRS in cancer patients with CRC. By integrating advanced techniques, we identified the FRS and revealed the intricate molecular landscape and diversity of the FRS within the TME. Notably, the FRS effectively predicted unfavorable prognosis and resistance to immunotherapy in CRC patients. Furthermore, PHA-793887, identified as a potential FRS inhibitor by the CTRP and PRISM databases, significantly restructured the immunosuppressive TME and enhanced the antitumor immune response, resulting in a reduced tumor burden in the MC38 murine tumor model.ConclusionTogether, these data support FRS positively correlates with poor prognosis and therapy resistance. The PHA-793887 could be a potential FRS inhibitor to improving the effectiveness of CRC management via bolstering antitumor immunity.